Perspectives of Jesus in the writings of Paul : a historical examination of shared core commitments with a view to determining the extent of Paul's dependence on Jesus - Schoberg, Gerry (James Clarke & Co, 2014)
The critical question of the relationship between Jesus and Paul has been well established in New Testament studies for over 150 years and needs to be addressed with all the tools of historical criticism that scholarship has developed. So states Gerry Schoberg at the beginning of this new and important work that carries out that important task. By coupling comparative instances in the gospels and the works attributed to Paul, Schoberg invites the reader to enquire more profoundly than in past studies as to the nature of the relationship between Jesus and the most dramatic of Christian converts.